Influence of Mn2+ Concentration and UV Irradiation Time on the Luminescence Properties of Mn-doped ZnS Nanocrystals - Thi, Tran Minh (Communications in Physics, 2009)
ZnS:Mn were prepared by wet chemical method with Mn doping concentration from 0 at% to 12 at%. The structure and particle size of the obtained powders were measured by X-ray diffraction (XRD) and scanning electron microscopy (SEM) and shown that all samples are single phase with sphalerite crystal structure and average particle size of about 5 - 7 nm. The dependence of Mn2+ ions doped concentration, and UV irradiation time on the luminescent intensity of ZnS:Mn nanocrystals was discussed.